Undoing species: towards a Queer feminist antiespecism (TEL Tempo, Espaço e Linguagem, 2019)
Abstract: This article addresses some convergences between animalist, feminist and sex-gender dissident stances. Following Paul B. Preciado, I will argue that feminism is not a humanism, in order to analyze some prejudices of certain anti-speciesism feminisms. Likewise, I will explore the capacity of the notion of "multispecies alliance" to re-configure networks of interdependence that demand the dismantling of the human device: its speciesist, ableist, racist and cis-heteropatriarchal production.Keywords: Feminisms. Queer theory. Animality. Posthumanism. Anti-speciesism.